Diverted Mini Gastric Bypass Surgery in Obese Population: Out-turn Over Hepatic and Nephrological Parameters - Singh, Arya; Ahmad, Rahnuma; Sinha, Susmita; Sinha, Susmita; Haq, Md Ahsanul; Narwaria, Mahendra; Haque, Mainul; Kumar, Santosh; Sanghani, Nandita (Bangladesh Journal of Medical Science, 2023)
Introduction: Bariatric surgery is the best possible option for reducing weight when lifestyle changes and medication have not brought about lasting success and may reduce morbidity and mortality. Weight loss that may follow bariatric surgery in patients on calory restricted diet would result in reduced inflammation and therefore lowering inflammation-related organ damage, including that of the kidney and liver. The study aimed to observe the consequences of BMI change on Hepatic and Nephrological parameters in patients after One Anastomosis Gastric Bypass surgery. Method: This study was done at a bariatric center with 150 individuals (both male and female) aged 20 to 60 years with obesity grades II and III who were selected randomly. Hepatic and renal function tests were carried out at baseline visit, then 3 months and 6 months following surgically. Result: Bilirubin level significantly increased from baseline to visit 1; Serum glutamic-pyruvic transaminase (SGPT) levels significantly decreased at visits 1 and 2. The albumin to Globulin ratio was significantly increased at visit 2 . Blood Urea level and serum creatinine level reduced considerably at visit 1 and decreased more at visit 2 from baseline. Conclusion: Bariatric surgery may be related to improvement in both hepatic and renal function. The improvement may be attributed to reduced inflammatory organ damage related to obesity. More such studies must be performed to highlight the possible health benefits of bariatric surgery for obese patients whose lifestyle modification and medication have not aided in weight loss. Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 743-758